Are screening instruments valid for psychotic-like experiences? A validation study of screening questions for psychotic-like experiences using in-depth clinical interview - Kelleher, Ian; Harley, Michelle; Murtagh, Aileen; Cannon, Mary (Schizophrenia bulletin, 2011)
Individuals who report psychotic-like experiences are at increased risk of future clinical psychotic disorder. They constitute a unique "high-risk" group for studying the developmental trajectory to schizophrenia and related illnesses. Previous research has used screening instruments to identify this high-risk group, but the validity of these instruments has not yet been established. We administered a screening questionnaire with 7 items designed to assess psychotic-like experiences to 334 adolescents aged 11-13 years. Detailed clinical interviews were subsequently carried out with a sample of these adolescents. We calculated sensitivity and specificity and positive predictive value (PPV) and negative predictive value (NPV) for each screening question for the specific symptom it enquired about and also in relation to any psychotic-like experience. The predictive power varied substantially between items, with the question on auditory hallucinations ("Have you ever heard voices or sounds that no one else can hear?") providing the best predictive power. For interview-verified auditory hallucinations specifically, this question had a PPV of 71.4% and an NPV of 90.4%. When assessed for its predictive power for any psychotic-like experience (including, but not limited to, auditory hallucinations), it provided a PPV of 100% and an NPV of 88.4%. Two further questions-relating to visual hallucinations and paranoid thoughts-also demonstrated good predictive power for psychotic-like experiences. Our results suggest that it may be possible to screen the general adolescent population for psychotic-like experiences with a high degree of accuracy using a short self-report questionnaire.